Non-invasive Ventilation and CPAP Failure in Children and Indications for Invasive Ventilation - Amaddeo, Alessandro; Khirani, Sonia; Griffon, Lucie; Teng, Theo; Lanzeray, Agathe; Fauroux, Brigitte (Frontiers in Pediatrics, 2020)
Noninvasive ventilation (NIV) and continuous positive airway pressure (CPAP) are effective treatments for children with severe sleep disordered breathing (SBD). However, some patients may present too severe SDB that do not respond to NIV/CPAP or insufficient compliance to treatment. A careful revaluation of the interface and of ventilator settings should be performed before considering alternative treatments. In patients with obstructive sleep apnea (OSA), alternatives to CPAP/NIV rely on the underlying disease. Ear-nose-throat (ENT) surgery such as adeno-tonsillectomy (AT), turbinectomy or supraglottoplasty represent an effective treatment in selected patients before starting CPAP/NIV and should be reconsidered in case of CPAP failure. Rapid maxillary expansion (RME) is restricted to children with OSA and a narrow palate who have little adenotonsillar tissue, or for those with residual OSA after AT. Weight loss is the first line therapy for obese children with OSA before starting CPAP and should remain a priority in the long-term. Selected patients may benefit from maxillo-facial surgery such as mandibular distraction osteogenesis (MDO) or from neurosurgery procedures like fronto-facial monobloc advancement. Nasopharyngeal airway (NPA) or high flow nasal cannula (HFNC) may constitute efficient alternatives to CPAP in selected patients. Hypoglossal nerve stimulation has been proposed in children with Down syndrome not tolerant to CPAP. Ultimately, tracheostomy represents the unique alternative in case of failure of all the above-mentioned treatments. All these treatments require a multidisciplinary approach with a personalized treatment tailored on the different diseases and sites of obstruction. In patients with neuromuscular, neurological or lung disorders, noninvasive management in case of NIV failure is more challenging. Diaphragmatic pacing has been proposed for some patients with central congenital hypoventilation syndrome (CCHS) or neurological disorders, however its experience in children is limited. Finally, invasive ventilation via tracheotomy represents again the ultimate alternative for children with severe disease and little or no ventilatory autonomy. However, ethical considerations weighting the efficacy against the burden of this treatment should be discussed before choosing this last option.